Youth-Perceived Burden of Type 1 Diabetes: Problem Areas in Diabetes Survey–Pediatric Version (PAID-Peds). (24th April 2015) - Markowitz, Jessica T.; Volkening, Lisa K.; Butler, Deborah A.; Laffel, Lori M. B.
Background: Management of type 1 diabetes in childhood can be challenging and overwhelming. Despite availability of advanced treatments and new technologies, the burden has not decreased as current approaches to intensive therapy are not without need for patient involvement. This study aimed to design and validate a measure of youth-reported burden related to type 1 diabetes management. Method: A multidisciplinary pediatric diabetes team designed the survey, based on a previously validated parent measure of diabetes-related burden (PAID-PR); survey revisions and pilot testing followed. The 20-item PAID-Peds assesses burden over the past month. Youth with type 1 diabetes (N = 126, ages 8-17, intensively treated with insulin pump therapy or multiple daily injections) completed the new survey, along with other surveys; parents completed companion measures. Electronic medical records and blood glucose meter download provided other salient data. Results: The PAID-Peds displayed excellent internal consistency (α = .94) and acceptable test–retest reliability (intraclass correlation .66, P < .0001). The PAID-Peds correlated significantly with both youth and parent reports of diabetes-specific family conflict, negative affect around blood glucose monitoring, depressive symptomatology, trait anxiety, and quality of life. It was not correlated with demographic or clinical characteristics of the youth. Conclusions: This new measure, the PAID-Peds, of youth-reported burden related to type 1 diabetes may have clinical and research utility, particularly in the current era of emerging diabetes technologies that require ongoing patient input.